Long-Term Exposure to Microplastics Promotes Early-Stage Hepatocarcinogenesis Induced by Diethylnitrosamine in Rats by Modulation of Their Gut Microbiota - Huina Guo; Jianan Wang; Shaowen Huang; Suren Rao Sooranna; Fangyi Shu; Genliang Li (Toxics)
Hepatocarcinogenesis is linked to environmental factors, with microplastics (MPs) emerging as a global environmental concern that may contribute to liver injury. However, the impact of MPs on the early stages of hepatocarcinogenesis has been largely ignored. Here we investigated the impact of long-term MP exposure on the formation of preneoplastic lesions during hepatocarcinogenesis induced by diethylnitrosamine (DEN) in rats. Rats were injected with DEN to induce preneoplastic lesions, and then they were orally administered with 1 µm MPs 0.5 mg/kg body weight per day for 20 weeks. The results revealed that long-term exposure to MPs did not induce the formation of glutathione S-transferase placental form (GST-P)-positive foci as preneoplastic lesions during hepatocarcinogenesis in these animals, thereby indicating non-carcinogenicity. However, MP exposure resulted in a 1-fold increase in both the number and size of GST-P-positive foci in rats initiated with DEN compared to those treated with DEN alone. Accordingly, MP exposure led to a 0.61-fold increase in the index of proliferating cell nuclear antigen (PCNA)-positive cells in DEN-initiated rats when compared to DEN treatment alone. In addition, the composition of the gut microbiota was significantly altered, accompanied by various levels of short-chain fatty acids. Our results suggest that long-term MP exposure can promote pre-neoplastic lesion formation in DEN-induced rats by increased cell proliferation as well as alterations in the gut microbiota and short-chain fatty acid levels. This highlights the potential health risks associated with hepatocarcinogenesis linked to long-term exposure to MPs.